Multilevel Converter by Cascading Two-Level Three-Phase Voltage Source Converter - Abdullrahman A. Al-Shamma’a (Department of Electrical Engineering, College of Engineering, King Saud University, Riyadh 11421, Saudi Arabia) (MDPI AG, 2018)
This paper proposes a topology using isolated, cascaded multilevel voltage source converters (VSCs) and employing two-winding magnetic elements for high-power applications. The proposed topology synthesizes 6 two-level, three-phase VSCs, so the power capability of the presented converter is six times the capability of each VSC module. The characteristics of the proposed topology are demonstrated through analyzing its current relationships, voltage relationships and power capability in detail. The power rating is equally shared among the VSC modules without the need for a sharing algorithm; thus, the converter operates as a single three-phase VSC. The comparative analysis with classical neutral-point clamped, flying capacitor and cascaded H-bridge exhibits the superior features of fewer insulated gate bipolar transistors (IGBTs), capacitor requirement and fewer diodes. To validate the theoretical performance of the proposed converter, it is simulated in a MATLAB/Simulink environment and the results are experimentally demonstrated using a laboratory prototype.